Sport-related anxiety and self-talk between traditional sports and esports - LeNorgant, E. J. (California State University, 2019)
The purposes of this thesis were to (1) examine trait and state sport-related anxiety, and (2) identify and compare the intensity and frequency of self-talk patterns of eSports competitors and traditional sport athletes. ESports have grown into a multimillion dollar industry. Competition prize pools, college scholarships, and corporate sponsorships suggest eSports are becoming a viable college and career opportunity that in turn places high psycho-emotional demands on competitors during training and competition. Sport psychology research has shown competition elicits high stress and anxiety in traditional sports (Ford, Ildefonso, Jones, & Arvinen-Barrow, 2017; Hanton, Mellalieu, & Williams, 2015). Also, anxiety has been found to have a significant adverse relationship to competitive sport performance (Woodman & Hardy, 2003). Therefore, it is hypothesized that there will be no significant difference between eSports and traditional sports competitors` sport-related anxiety scores. Also, no significant difference between groups` self-talk intensity and frequency is expected. Thirty-three eSport and 56 traditional sport competitors who compete for a NCAA Division I, II, or NAIA institution participated in this study. At Time 1, participants completed the demographics, SAS-2, STQ and TOPS questionnaires. At Time 2, within 24 hours of competition, participants completed the CSAI-2R(d), S-TQ, and TOPS. Analysis of data showed no support for the null hypotheses expected for this study. Discussion provides directions for future studies.